2015
DOI: 10.4238/2015.june.8.8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of quantitative trait loci for main plant traits in soybean

Abstract: ABSTRACT. Plant traits are important indices for regulating and controlling yield ability in soybean varieties. It is important to comprehensively study the quantitative trait locus (QTL) mapping for soybean plant traits, cloning related genes, and marker assistant breeding. In this study, 236 F 2 generation plants and a derivative group were constructed by using Jiyu50 and Jinong18, obtained from Jilin Province. A total of 102 simple sequence repeat markers were used to construct a genetic linkage map. With 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 12 publications
3
38
0
6
Order By: Relevance
“…In previous linkage QTL mapping studies, approximately 93 QTLs were identified for branch number, which were distributed on all 19 chromosomes. Most of these QTLs showed relatively small effects, with only two major QTLs [17, 20], on the C1 and C2 chromosomes, respectively. Comparison of the regions of the QTLs detected in this study and meta-QTL for branch number reported by predecessor showed that qBN.A1 , qBN.C2 and qBN.F included meta-QTL, suggesting these three QTLs may have a robust effect on branch number in different genetic backgrounds if they are identical to these meta-QTL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous linkage QTL mapping studies, approximately 93 QTLs were identified for branch number, which were distributed on all 19 chromosomes. Most of these QTLs showed relatively small effects, with only two major QTLs [17, 20], on the C1 and C2 chromosomes, respectively. Comparison of the regions of the QTLs detected in this study and meta-QTL for branch number reported by predecessor showed that qBN.A1 , qBN.C2 and qBN.F included meta-QTL, suggesting these three QTLs may have a robust effect on branch number in different genetic backgrounds if they are identical to these meta-QTL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that branch number is controlled by multiple quantitative trait loci (QTLs), and almost 93 branch number QTLs have been identified from nearly 18 linkage mapping populations [9–20]. Interestingly, a few QTLs on the C2 chromosome were found to be concentrated in a region (103-121cM) derived from different parents and environments [4, 21–25].…”
Section: Introductionmentioning
confidence: 99%
“…Hwang (2010) Chapman et al 2003;Chung et al 2003;Nichols et al 2006;Bachlava et al 2009;Kuroda et al 2013;Hu et al 2014;Qi et al 2014a). Os QTLs identificados no GL I, por Hu et al 2014 (Mansur et al 1993;Lark et al 1994;Lark et al 1995;Mansur et al 1996;Orf et al 1999;Specht et al 2001;Wang et al 2004;Zhang et al 2004;Hwang 2010 (Lee et al 1996;Kim et al 2012), no GL C2 (Specht et al 2001;Wang et al 2004;Zhang et al 2004;Reinprecht et al 2006;Gai et al 2007;Palomeque et al 2009b;Liu et al 2011;Rossi et al 2013;Lee et al 2015), no GL D2 (Kim et al 2012), no GL I Chapman et al 2003), no GL J (Sun et al 2006) e no GL M (Specht et al 2001;Wang et al 2004;Zhang et al 2004;Pathan et al 2013;Yao et al 2015 (Mansur et al 1996;Zhang et al 2004;Sun et al 2006;Josie et al 2007;Palomeque et al 2009b;Hwang 2010;…”
Section: Mt-mim: Multiunclassified
“…Os QTLs descritos nessa região associados às pragas e doenças afetam a resistência da soja ao nematoide de cisto Heterodera glycines (Glover et al 2004;Guo et al 2006;Chang et al 2011;Ferreira et al 2011;Jiao et al 2015) , a Phytophthora sojae, (Weng et al 2007;Tucker et al 2010), ao vírus do mosaico comum (VMCS) (Yan et al 2015) e à podridão parda-da-haste (Phialophora gregata) (Lewers et al 1999;Patzoldt et al 2005a;Patzoldt et al 2005b (Wang et al 2004;Rossi et al 2013;Sun et al 2013;Yao et al 2015), um QTL no GL D2 (Kim et al 2012), e QTLs no GL M (Specht et al 2001;Wang et al 2004;Zhang et al 2004) (Keim et al 1990;Orf et al 1999;Kim et al 2012), quanto para a região revelada no subgrupo C1-2 (Orf et al 1999;Zhang et al 2004;Rossi et al 2013;Sun et al 2013). Kim et al 2012), e também para a região identificada no subgrupo C1-2 (Yuan et al 2002;Rossi et al 2013), no GL C2 (Zhang et al 2004;Reinprecht et al 2006;Gai et al 2007;Du et al 2009;Rossi et al 2013;Yao et al 2015), no GL D2 (Kazi et al 2010;Qi et al 2014a), no GL F (Reyna and Sneller 2001;Rossi et...…”
Section: Mt-mim: Multiunclassified
See 1 more Smart Citation